2012
DOI: 10.1139/t11-105
|View full text |Cite
|
Sign up to set email alerts
|

Small-strain stiffness of Zenoz kaolin in unsaturated conditions

Abstract: An experimental study has been carried out to investigate the effects of isotropic compression, wetting, and drying on the initial shear stiffness of Zenoz kaolin, an unsaturated lean clay, both in normally consolidated and overconsolidated conditions. The proposed study was conducted using fixed–free resonant column – torsional shear (RCTS). Specimens were compacted using the undercompaction technique. Initial shear stiffness was measured almost continuously along complex stress paths including (i) an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 11 publications
1
12
2
Order By: Relevance
“…In the low suction range before AEV, the shear modulus increases linearly with suction, after which its increase is predominantly non-linear, mainly due to the distinct hydraulic regulation at the particle level (Mancuso et al, 2002). Similar observations were also reported for a range of different soils by Marinho et al (1996); Vinale et al (2001), Inci et al (2003), Sawangsuriya et al (2008), Biglari et al (2012) and Heitor et al (2012). In addition, Mancuso et al (2002) and, more recently, Heitor et al (2013) also reported that the small strain shear modulus depends mainly on the soil fabric derived from compaction, that is, dry and wet of optimum water content particularly in the macroporosity range.…”
Section: Introductionsupporting
confidence: 77%
“…In the low suction range before AEV, the shear modulus increases linearly with suction, after which its increase is predominantly non-linear, mainly due to the distinct hydraulic regulation at the particle level (Mancuso et al, 2002). Similar observations were also reported for a range of different soils by Marinho et al (1996); Vinale et al (2001), Inci et al (2003), Sawangsuriya et al (2008), Biglari et al (2012) and Heitor et al (2012). In addition, Mancuso et al (2002) and, more recently, Heitor et al (2013) also reported that the small strain shear modulus depends mainly on the soil fabric derived from compaction, that is, dry and wet of optimum water content particularly in the macroporosity range.…”
Section: Introductionsupporting
confidence: 77%
“…Although studies of dynamic soil properties within the laboratory environment, e.g. resonant column testing, have been performed for several decades, the effects of saturation, particle size and shape, gradation and matrix suction were not investigated until the early 1980s (Wu et al 1984;Qian et al 1991;Wheeler et al 2003;Biglari et al 2012). Further, very little research has been performed on anisotropic shear moduli for unsaturated soils (Ng and Yung 2008;Ng et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It means that the compacted specimen has initial suction level higher than 150 kPa and lower than 300 kPa. Initial suction of these ideal samples were measured by [6] at 240 kPa. In Figures 5 and 6 the specific volume changes (dv) of the samples are plotted versus the time in the suction levels of 150 kPa and 300 kPa for the slow and the high rate tests, respectively.…”
Section: Resultsmentioning
confidence: 99%